THE INFLUENCE OF PROFITABILITY AND LEVERAGE ON CORPORATE SOCIAL RESPONSIBILITY - Iswara, Ulfah Setia; Widyawati, Dini; Setyabudi, Teguh Gunawan; ., Susanti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
This research aims to empirically test and analyze the influence of profitability and leverage on corporate social responsibility. This research includes quantitative research. The research sample was 97 mining companies listed on the Indonesia Stock Exchange in the period 2018 to 2022. The sampling technique used purposive sampling. Profitability is measured using Return on Assets (ROA), leverage is measured using the Debt to Equity Ratio (DER), and corporate social responsibility is measured using the corporate social responsibility disclosure index (CSRDI). The data used is company annual financial report data. The data analysis technique was carried out using multiple linear regression analysis and data processing via SPSS. The research results show that profitability has a significant positive effect on the company's corporate social responsibility. Leverage has also been proven to influence a company's corporate social responsibility. Companies that are able to generate profits (profits) and manage debt well will have an impact on the corporate social responsibility of mining companies listed on the Indonesia Stock Exchange.